1997
DOI: 10.1088/0031-9155/42/11/012
|View full text |Cite
|
Sign up to set email alerts
|

A study of thyroid radioiodine monitoring by Monte Carlo simulations: implications for equipment design

Abstract: Monte Carlo simulations have been performed to evaluate the design of collimated detectors used to measure 125I or 131I in the thyroid gland. Two detector sizes were simulated for each radioisotope: (i) for 125I monitoring 2.54 cm diameter and 7.62 cm diameter and 0.2 cm thickness and (ii) for 131I monitoring 2.54 cm diameter, 3.2 cm thickness and 7.62 cm diameter, 6.4 cm thickness. The virtual thyroid gland was 20 g. Activity was placed in both the gland and the remainder of the body in varying amounts to ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Monte Carlo simulations have also been performed to evaluate the design of collimated detectors used to measure 125 I or 131 I in the thyroid gland. 124 Two detector sizes were simulated for each radioisotope and activity was placed in both the gland and the remainder of the body in varying amounts to assess the efficacy of collimation. This study showed that a wide angle of acceptance and sufficient detector crystal thickness take precedence over collimation and shielding.…”
Section: B Imaging Systems and Collimators Designmentioning
confidence: 99%
“…Monte Carlo simulations have also been performed to evaluate the design of collimated detectors used to measure 125 I or 131 I in the thyroid gland. 124 Two detector sizes were simulated for each radioisotope and activity was placed in both the gland and the remainder of the body in varying amounts to assess the efficacy of collimation. This study showed that a wide angle of acceptance and sufficient detector crystal thickness take precedence over collimation and shielding.…”
Section: B Imaging Systems and Collimators Designmentioning
confidence: 99%
“…For example, Monte Carlo simulations have been used in the following: help users determine the optimum detector size for thyroid monitoring of workers occupationally exposed to either 125 I or 131 I (1); to determine the effect of counting geometry on thyroid monitoring for 131 I (2); to determine the effect of a heterogeneous aerosol deposition on the activity estimate obtained using a lung counter that was calibrated assuming a homogeneous deposition (3); and to determine the effect of counting geometry on thyroid monitoring for 125 I (4). Some other examples (5,6) of the impossible that have been investigated by the HML include: removing the ribs from a phantom's chest to assess the impact of photon blockage by ribs at various photon energies; using photon energies for which there is no physical equivalent to fill in areas covered by physical equivalents; changing the chest depth profile of a phantom; extending the adipose content to values not physically achievable; and evaluating the effect of 131 I distribution on a counting system. In all of the above studies the code used was MCNP (Monte Carlo NParticle transport system).…”
Section: Introductionmentioning
confidence: 99%